Arrangement of Sounds Product in the Middle of the Tongue (ج ش ى) - Mohamed, Ahmed; Ahmed, Ayman (Dirasat: Human and Social Sciences, 2020)
The study is an attempt to get benefit of the advancement in the technology of studying human sounds, especially acuastic phonetic to identify accurately the arrangement of sounds product in the middle of the tongue (ج ش ي) in Arabic . It was, and still, a debatable issue among old and modern phoneticians about how these sounds are arranged to locate accurately place of articulation. The variable this study based on the duration of time from the most clarity of articulating the sound to the most clarity of alfataha that follows the sound in the collected data. It is to compare between duration of time to know which one lasts more than the others, the more time a sound lasts, the farther it should be. In Arabic phonology , what follows a focused sound is know in the speech chain ( the voiced fataha ) in these studied samples. It is concluded that (الجيم والشين) are produced in the same place of articulation. The only difference 13 represented by the effort in (الجيم) and the devoid (الشين) but the short (الياء) is the farthestamong the sound produced in the middle of the tongue and nearer than (الجيم) and (الشين) to the to the fauces